Telehealth transition in a comprehensive care unit for eating disorders: Challenges and long‐term benefits. Issue 11 (27th July 2020) - Datta, Nandini; Derenne, Jennifer; Sanders, Mary; Lock, James D.
Abstract: The 2019 novel coronavirus disease (COVID‐19) pandemic has forced many eating disorder medical stabilization units to consider adjustments that uphold both the quality of care delivered to patients while also observing social distancing public health directives for patients and staff. To date, inpatient facilities for eating disorders (both medical stabilization units and higher level of care facilities) have not needed to consider how to translate services to electronic platforms, given that most of these programs have in‐person staff. We outline our transition to telehealth broadly, emphasizing some unexpected benefits of using telehealth services that we plan on integrating into our work‐flow post COVID‐19. These may be useful for other higher level of care eating disorder programs, including medical stabilization units, residential, partial hospitalization, and intensive outpatient programs. We also highlight aspects of transition that have been more challenging for this particular patient population, warranting the need for in‐person services.